Q: 2x - 3y equals 4 and x plus 4y equals -9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

It is the same as: 6x+4y

y=2

Related questions

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

Let's simplify this together, friend. First, we add the terms with 'x' together: 2x - 5x = -3x. Then, we add the terms with 'y' together: 4y + 3y = 7y. So, the expression simplifies to -3x + 7y. Remember, there are no mistakes, just happy little accidents in math!

6x plus 4y

10x+2x-3y-4y=12x-7y

If: 2x-3y = -15 and x = 4y Then: x = -12 and y = -3

The ordered pair is (-1, -2).

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

It is the same as: 6x+4y

4x + 3y - 2x - 7y2x - 4y

3x + 7y

4y + 4 = 3y - 5 y = -9